Comatose within 6 weeks, but still alive after 3 years, Creutzfeldt‐Jakob disease with unusual progression. Issue 6 (19th April 2020) - Christopher, Julia Kathleen; Khong, Brian; Abolfazli, Amin; Liu, Antonio
Abstract: Creutzfeldt‐Jakob disease (CJD) should still be considered in a patient presenting with rapidly progressive dementia and negative CSF 14‐3‐3 protein and RT‐QulC. Treatable causes of encephalopathy must be ruled out. Neurodegenerative diseases must also be considered. Abstract : Creutzfeldt‐Jakob disease (CJD) should still be considered in a patient presenting with rapidly progressive dementia and negative CSF 14‐3‐3 protein and RT‐QulC. Treatable causes of encephalopathy must be ruled out. Neurodegenerative diseases must also be considered.